Endothelial alterations in systemic lupus erythematosus and rheumatoid arthritis : potential effect of monocyte interaction (2017)
ABSTARCT: Patients with systemic autoimmune diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) are prone to develop atherosclerosis and cardiovascular diseases five times more often than the general population; this increase in frequency could be partially explained by an increase in the macrovasculature endothelial damage. In these autoimmune diseases, a microvascular endothelial injury has also been reported in different organs and tissues, especially in sites where ultrafiltration processes occur. Different components that are characteristic to the immunopathology of RA and SLE could be involved in the endothelial cell activation, permeability increase, functional alteration, and vascular injury. Circulating immune complexes (IC) detected in SLE and RA have been proposed to participate in the endothelial injury. In the vascular environment, IC can generate different responses that could be mediated by monocytes, because these cells have patrolling and monitoring functions on the endothelium. However, with certain stimuli such as TLR ligands, the monocytes are retained in the lumen, releasing proinflammatory mediators that participate in the endothelial damage. This paper aims to review some aspects about the endothelial activation and dysfunction in the context of SLE and RA, as well as the potential role that monocytes apparently play in this process